The Role of Sharia-Based Non-Bank Financial Institutions in Supporting Islamic Banking in Indonesia - Fadhil, Muhammad; Andrini, Rozi; Afifah, Dhiya Dwi (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
The Islamic non-bank financial Industry (NBFI syariah) plays an important role in supporting the growth and strengthening of Islamic banking in Indonesia. The existence of NBFI syariah, such as Islamic insurance, Islamic financing, Islamic pension funds, and Islamic capital markets, is an integral part of the national Islamic financial ecosystem. This article aims to analyze the strategic contribution of NBFI syariah in supporting the development of Islamic banking through a descriptive-qualitative approach based on literature reviews and secondary data from the Financial Services Authority (OJK), Bank Indonesia, and other relevant institutions. The findings indicate that Islamic non-bank financial institutions expand the reach of Islamic financial services, enhance financial literacy and inclusion, and provide alternative financing and risk mitigation options in line with Islamic principles. Synergistic collaboration between Islamic banking and non-banking financial institutions is considered capable of strengthening the overall stability of the Islamic financial system. Therefore, strengthening regulations, improving institutional capacity, and product innovation are key to optimizing the role of Islamic non-bank financial institutions in promoting inclusive and sustainable Islamic banking growth in Indonesia.